The Influence of Service Quality, Promotion, and Knowledge about Al Wadi'ah Products on Customers' Decision to Save in Islamic Banks - Susanti, Dwi; Purnamasari, Femei; Hasyim, Diah Mukminatul (Al-Mashrof: Islamic Banking and Finance, 2023)
This study aims to determine the effect of service quality, promotion, and knowledge of Al-Wadi'ah products on customers' decisions to save at Bank Syariah Indonesia KCP Kedaton Bandar Lampung. This study uses a type of quantitative research, with data sources namely primary data. The number of samples in this study was 100 respondents, namely BSI customers who used Wadi'ah savings products, and where the research was conducted at BSI KCP Kedaton Bandar Lampung. The results of the research on the t-test for the service quality variable obtained a calculated t value of 2,919 which was greater than the table t value of 1,988. and for the significance value obtained a value of 0.04 <0.05, the promotion variable obtained a t-value of 1.383 which was smaller than the T-table value of 1.988, and for significance obtained a value of 0.170> 0.05, Variable Knowledge of Al-Wadi'ah products Value obtained t Count of 0.797 is smaller than the t-table value, which is 0.560, which is smaller than the t-table value, which is 1.988. For significance, the value is 0.577 > 0.05.